THE DYNAMICS OF LEVERAGE AND PROFITABILITY: A COMPREHENSIVE REVIEW OF PRE-TAX EARNINGS - ghozali, diana atika (Tax Accounting Applied Journal, 2023)
This study investigates the relationship between leverage, profitability, and tax avoidance within the Indonesian banking sector. Utilizing a sample of 48 banks from 2010 to 2022, the study employs a simultaneous equation model to analyze how leverage, measured by Debt-to-Equity Ratio (DER), and profitability, measured by Return on Assets (ROA), influence tax avoidance, represented by the Effective Tax Rate (ETR). The findings reveal that leverage does not have a significant impact on tax avoidance, likely due to high variability in ETR and other dominant factors such as company-specific tax policies and strategies. In contrast, a significant negative relationship is observed between profitability and ETR, indicating that more profitable banks tend to engage in greater tax avoidance. This can be attributed to economies of scale, where larger and more profitable banks can distribute the fixed costs of tax avoidance strategies more efficiently. These results highlight the importance of considering tax avoidance in financial analysis and policy-making, suggesting further longitudinal studies and cross-sector comparisons to enhance understanding of these dynamics